Learning proficiency of life (soft skill) through the healthy canteen model (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2020)
Currently, the government emphasizes that school activities that require a clean and healthy lifestyle are in services and activities in the school canteen. The school canteen at MIS Al Hidayah Medan is currently in an inadequate condition due to limited facilities. In order to achieve the title of Adiwiyata School, it is necessary to manage a Healthy Canteen. The quality of the canteen was improved through the 2020 USU TALENTA Community Service Program. The output of this service becomes a learning proficiency of life (Soft Skills) through the Healthy School Canteen which can be duplicated into a teaching manual as well as being a reference for planning experts (architects, interior planners) and design guides for determinants. Healthy Canteen policy as an alternative to overcome the limitations of learning spaces by making the canteen as a study room.